Impact of Hot Deformation Methods on Metal Workability along the Section During the Production of Axle Billets - Babachenko, O. I; Balakhanova, T. V; Safronova, O. A.; Kononenko, H. A; Domina, K. H (Science and Transport Progress, 2021)
Purpose. The work is aimed to determine the influence of various technologies for the production of rough railroad axles from F grade carbon steel on the workability features along the section in order to improve the quality of railway axles at domestic enterprises. Methodology. Four production technologies of the rough railway axles were analyzed. The peculiarity of the study was that the technologies differed only in the deformation pattern. The dimensions of the initial continuously cast billets and the resulting rough axes were the same for all deformation modes. The chemical composition and temperature of deformation also did not differ. The density of traces of the dendritic structure was taken as the main metallographic characteristic, which makes it possible to assess the degree of deformation workability of the rough axes along the section. The analysis was performed on templates cut from each section of the axle. The workability of the metal was assessed by the transformation of traces of the dendritic structure (liquation areas). The dendritic structure, namely its density, was determined as the number of dendrites per 1 mm2 of the microsection area, and to accurately calculate the dendrite size, measurements were made at least along two ellipse axes– large and small. Findings. It is shown that, despite a significant degree of forging of axle billets made of carbon steel, when using different deformation schemes, their workability along the section differs significantly. The most effective production technology of rough railroad axles from F grade carbon steel has been determined from the point of view of workability along the section of rolled stock, and the impact of each of the investigated deformation methods has been assessed. The largest and the smallest workability coefficients of the axle billet have been established when using various methods of deformation impact. Originality. The production technology of rough railway axles has been determined, which ensures the most uniform workability of rolled products along the section. Practical value. The workability factor for a quantitative assessment of the effect of hot deformation was determined and the formation pattern of the dendritic traces’ density in the direction from the surface to the central layers of the workpiece was established.